ACCEPTANCE OF WEB-BASED TECHNOLOGY AS A HARMONIOUS COMMUNITY OF CITIZEN WITH THE CONCEPT OF TECHNOLOGY MODEL ACCEPTANCE - Riki - Riki (Jurnal TAM (Technology Acceptance Model), 2019)
The internet in this era is a way of communicating the most quickly and effectively in disseminating information. Through the internet, various information can be received using several ways, such as websites, email and others. To determine the success or failure if an application of information technology, a Technology Acceptance Model was developed based on Theory of Reasoned Action to explain and predict the acceptance of technology by users. This model places the factors of attitude, intention and behavior of users by using 2 main input variables, namely usefulness and easy of use. Empirically this model has been shown to provide an overview of the behavior of information technology users, here we analyze to determine the level of acceptance of website usage in modeling the Structural Equations by users identifies through the user’s perceptions and behavior in using the website